From ‘activity’ to ‘labour’: commodification, labourpower and contradiction in Engeström’s activity theory - Warmington, Paul (Outlines. Critical Practice Studies, 2008)
Engeström’s (1987, 1999) innovations in cultural-historical activity theory emphasise the role of contradictions in analysing and transforming learning in practice. This paper considers some of the problems and possibilities contained in his analytical understanding of contradictions, in relation to activity and to what he terms ‘expansive learning’ (Engeström, 2001, 2004, 2007). In doing so, it builds upon Engeström’s stated concern with theorising activities ‘in capitalism’. Its goal is to problematise the underlying practical definition of contradictions and the claims made for his ‘contradiction-driven’ analysis of work practices as a platform for transformation. This paper suggests that the definition of contradictions that underpins Engeström’s notions of ‘expansive’ learning and his ‘developmental work research’ methodology is restrictive because it underplays the wider social contradictions and antagonisms inherent in the commodification of labour-power. As such, while Engeström’s take on activity theory offers a valuable approach to reforming configurations of labour within the bounds of capitalist efficiency, its engagement with capitalism’s internal contradictions is uneven and, therefore, its claims to produce transformative, expansive learning are heavily qualified. The framework of this argument is provided by Postone’s (1996) reading of Marx’s Capital and Grundrisse as social theories of labour within capitalism and the extensive analyses of the social reproduction of labourpower developed by Rikowski (1999, 2000a, 2000b, 2002a, 2002b), Allman et al. (2000) and Dinerstein and Neary (2002). The paper ends with a consideration of the practical research possibilities emanating from its call to ground activity theory and its concern with contradictions in a sophisticated understanding of labourpower theory. It draws upon the UK-based Learning in and for Interagency Working Project’s (2004‑2008) intervention research in multiprofessional children’s service settings. It discusses the project’s rethinking of the notion of contradictions, the need to understand the division of labour as a tool in the social production of labour-power and the sense in which historical shifts in the ways that institutions organise collective labourpower make visible the social production of labourpower as an object of activity.